2008
DOI: 10.1111/j.1365-2850.2008.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining equilibrium: a theory of job satisfaction for community mental health nurses

Abstract: This study aimed to explore what was satisfying in the role of community mental health nurse (CMHN). Previous studies have emphasized sources of dissatisfaction but the emphasis on satisfaction allowed the researchers to explore positive aspects of the role which have been largely neglected in previous studies and to explore how these nurses managed to sustain satisfaction. This study used a grounded theory, and the primary source of data was in-depth interviews collected over a 1-year period with 12 CMHNs. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Such positive team support has been shown to create open discussions between team members in previous research (Jezuit , Apker et al . , Wilson & Crowe ).…”
Section: Discussionmentioning
confidence: 98%
“…Such positive team support has been shown to create open discussions between team members in previous research (Jezuit , Apker et al . , Wilson & Crowe ).…”
Section: Discussionmentioning
confidence: 98%
“…This might prove to be important for the retention of healthcare professionals. Colleagues are an important source for social support and it could be shown that support by colleagues is a protective factor against burnout and can prevent absenteeism (van der Heijden et al., ); belonging to a team is important for job satisfaction (Wilson & Crowe, ). This is also corroborated by the results obtained from the evaluation of working atmosphere: Participants judged a good working atmosphere in the community mental health team as very important.…”
Section: Discussionmentioning
confidence: 99%
“…Each population should guide the researcher closer to the central idea of the theory (Glaser , ). Wilson and Crowe demonstrated a strong example of theoretical sampling in their grounded theory of job satisfaction for community mental health nurses, stating: ‘The first three interviews kept a general focus and after these were analysed the emerging concepts formed the basis of the next three interviews and this process was repeated until it appeared that saturation was achieved’ (Wilson & Crowe , p. 817).…”
Section: Overview Of Classic Grounded Theory Methodologymentioning
confidence: 99%
“…Good grounded theory studies have grab and fit, and the reader finds him or herself nodding along in agreement. While reading Wilson & Crowe's () grounded theory of maintaining equilibrium among community mental health nurses, the reader readily understands how therapeutic relationships moderate job satisfaction against the pressures of role performance in this community. Wilson & Baker () effectively explain how Maori mental health nurses bridge the Maori world and the mainstream health services world by ‘going beyond’ and ‘practicing differently’.…”
Section: Implications For Practicementioning
confidence: 99%